A preliminary isotope-based evapotranspiration partitioningapproach for tropical Costa Rica - Iraheta, Alberto (2021)
Spatially and seasonally distributed information on transpiration (T) fluxes is limited in the tropics. Here, we applied a coupled isotope mass balance model to separate water fluxes of T and evapotranspiration (ET) from precipitation (P). The mean annual T was estimated at a resolution of 100 m for Costa Rica (51,100 km2) and a partitioning of monthly T and evaporation (E) for the 2370-km2 San Carlos catchment. The dominant flux in the forest ecosystems was T with a mean annual T of 1086 mm that ranged from 700 mm in Tropical Montane Very Humid Forest to 1400 mm in Subtropical and Tropical Low Montane Rainforests. We estimated an average 85% of ET was T, which is concurrent with expectations for forested tropical regions, but varied according to model parameterization and data sources. A model comparison exercise showed a range of mean annual T estimates from 988 to 1465 mm and a range of T/P from 0.35 to 0.5 with temperature and relative humidity exhibiting the highest impact on the model results. Across Costa Rica, we estimated an average loss of precipitation by T of 38% (1085 mm), whereas interception (I) constitutes 10% (230 mm) and direct evaporation (E) only 7% (192 mm). Similarly, the results at the catchment scale indicated that monthly T contributes 76% (85-mm monthly average) to total ET and E corresponds to 24% (24-mm monthly average). The T rates exhibited an opposite seasonality to rainfall with highest T over the drier months from December to April with a peak in March (101–144 mm) and the minimum T in September (53–71 mm). Around 17% (79–130 mm) of precipitation over the catchment area is lost to T, both E (10–35 mm) and I (15–38 mm) correspond to 5%. Despite the inherent uncertainties of the data assumptions and simplifications, including data interpolation errors, the coupled isotope mass balance model showed in comparison to other global products reasonable water partitioning for different ecosystems in Costa Rica and the San Carlos catchment area. These results can help to evaluate the impact of land cover conversion on the hydrological cycle in Costa Rica, and the simple isotope-based model could be transferred to different biomes of the tropics.